Formulación de lineamientos de diseño de sistemas basado en el internet de las cosas para la clasificación de residuos sólidos. - Guaranga Otavalo, Ebert Steeven (2024)
Given the growing problem of inadequate solid waste management, which contributes significantly to environmental pollution and the deterioration of human health [1], this research develops guidelines for the design and development of waste classification systems based on the Internet of Things. Things (IoT). In this way, the efficiency and effectiveness of solid waste classification is improved, thus reducing the negative environmental impact and optimizing waste management in urban contexts [2]. The methods used to develop these guidelines include a systematic literature review by Barbara Kitchenham [3], which identified and evaluated existing waste sorting technologies using IoT. Furthermore, the TDDM4IoTS methodology [4] is used for the design of the IoT waste classification system, ensuring a structured and systematic approach in the development of the prototype. Finally, evaluations are carried out to corroborate the efficiency and acceptance of the prototype. The results indicate that ultrasonic sensors are reliable for measuring both long and short distances, while infrared sensors have limitations in detecting transparent materials such as glass. The proposal of the design guidelines applied in a prototype has proven to be accepted by users. These results are essential to validate the applicability of the proposed guidelines and to highlight the continuous improvement of waste management systems through IoT technologies. Providing a solid foundation for the design of more efficient and effective waste classification systems. The developed guidelines not only facilitate technological implementation in waste management, but also offer guidelines for future research and development in the field. Continued exploration of new technologies, sensors and their integration into IoT systems is recommended to expand waste sorting capabilities.